2014
DOI: 10.1111/eci.12338
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation protein products and ischaemia‐modified albumin in obstructive sleep apnea

Abstract: We conclude that high systemic oxidative stress in obstructive sleep apnea is reflected by increased advanced oxidation protein products without causing an increase in ischaemia-modified albumin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 39 publications
(84 reference statements)
1
19
0
Order By: Relevance
“…Similarly, Uygur et al [28] also observed that serum IMA concentrations were significantly higher in the OSA group than in the control group, and serum IMA concentrations correlated with the AHI, mean SaO 2 , desaturation index, and C-reactive protein concentrations. In contrast, Ozben et al [29] did not observe any significant difference between OSA and control groups in terms of IMA levels. On the other hand, while IMA has been associated with obesity in the previous studies like IL-6, Yang et al did not assess the influence of obesity on IMA [10].…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Similarly, Uygur et al [28] also observed that serum IMA concentrations were significantly higher in the OSA group than in the control group, and serum IMA concentrations correlated with the AHI, mean SaO 2 , desaturation index, and C-reactive protein concentrations. In contrast, Ozben et al [29] did not observe any significant difference between OSA and control groups in terms of IMA levels. On the other hand, while IMA has been associated with obesity in the previous studies like IL-6, Yang et al did not assess the influence of obesity on IMA [10].…”
Section: Discussionmentioning
confidence: 80%
“…However, its possible role in OSA had not been clearly demonstrated yet. The number of studies focusing on this issue in the literature is limited [10,11,[26][27][28][29]. Yang et al [10] demonstrated a positive correlation between IMA levels and the OSA severity.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous study, we detected high systemic oxidative stress as reflected by increased advanced oxidation protein products, total oxidative status and reduced total antioxidative capacity with no marked change in ischaemia-modified albumin (IMA) levels in obstructive sleep apnoea syndrome (OSAS) [93]. Further studies performed after our study reported significantly increased IMA levels and oxidative stress which decreased after continuous positive airway pressure [94][95][96][97].…”
Section: Advanced Oxidation Protein Products and Ischaemia-modified Amentioning
confidence: 64%
“…Eccentric nondilated LVH does not predict adverse outcomes X [93] We conclude that high systemic oxidative stress in obstructive sleep apnoea is reflected by increased advanced oxidation protein products without causing an increase in ischaemia-modified albumin X [98] Based on our results and the high prevalence of multiple arteries, it seems reasonable not to exclude patients with multiple renal arteries from renal denervation (RDN). Current analysis suggests that blood pressure (BP) reduction may be less pronounced in patients with multiple renal arteries of whom not all arteries were treated Other n = 1…”
Section: Appendixmentioning
confidence: 81%
“…The pathophysiological events of ischemia, including hypoxia and free oxygen radicals changed the N-terminus of albumin, and this molecule is called as IMA [6]. IMA was first discribed as a marker of myocardial ischemia, but now it has been shown that elevated in various states of noncardiac ischemia and oxidative stress conditions such as cerebrovascular diseases, inflammatory bowel diseases, chronic liver diseases, obstructive sleep apnea (OSA) and pulmonary embolism [7][8][9][10][11][12][13].Additionally, it was suggested to be a strong indicator of short-term mortality in patients with end-stage renal disease [14] and myocardial infarction with ST elevation [15].…”
mentioning
confidence: 99%